2019
DOI: 10.1152/ajpendo.00474.2018
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational impact of maternal obesogenic diet on offspring bile acid homeostasis and nonalcoholic fatty liver disease

Abstract: Studies show maternal obesity is a risk factor for metabolic syndrome and nonalcoholic fatty liver disease (NAFLD) in offspring. Here we evaluated potential mechanisms underlying these phenotypes. Female C57Bl6 mice were fed chow or an obesogenic high-fat/high-sucrose (HF/HS) diet with subsequent mating of F1 and F2 female offspring to lean males to develop F2 and F3 generations, respectively. Offspring were fed chow or fibrogenic (high transfat, cholesterol, fructose) diets, and histopathological, metabolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
(60 reference statements)
0
21
0
Order By: Relevance
“…In the maternal HF/HS diet model, a similar degree of steatosis occurs in F2 and F3 offspring, suggesting that the maternal HF/HS diet does not have a transgenerational impact on steatosis. ( 21 ) Barbosa et al showed no increase in intrahepatic TG levels in F2 offspring from a paternal HFD lineage. In fact, after offspring HFD feeding, intrahepatic TG levels increased to a lesser degree than control mice.…”
Section: Multigenerational Transmission Of Phenotypesmentioning
confidence: 97%
See 2 more Smart Citations
“…In the maternal HF/HS diet model, a similar degree of steatosis occurs in F2 and F3 offspring, suggesting that the maternal HF/HS diet does not have a transgenerational impact on steatosis. ( 21 ) Barbosa et al showed no increase in intrahepatic TG levels in F2 offspring from a paternal HFD lineage. In fact, after offspring HFD feeding, intrahepatic TG levels increased to a lesser degree than control mice.…”
Section: Multigenerational Transmission Of Phenotypesmentioning
confidence: 97%
“…Offspring from a maternal obesogenic lineage were protected from fibrosis across all three generations. ( 21 ) The mechanism for this transgenerational effect has not been defined. However, one male lineage transmitted fibrosis protection across multiple generations in association with epigenetic changes in Pparγ .…”
Section: Multigenerational Transmission Of Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although epigenetics, microbiome, and metabolome were all considered the potential mechanisms, the specific mechanism of the “fetal programming” is still largely unclear (Wankhade et al, 2016). Substantial research and our previous studies both showed that early-life overnutrition-maternal high-fat diet during pregnancy and lactation significantly increased susceptibility to glucose intolerance, insulin resistance and lipid disorders in adult offspring (Zheng et al, 2016; Huang et al, 2017; Thompson et al, 2019). Therefore, early-life might be a critical window for preventing the transmission of metabolic diseases across generation and reducing the prevalence of T2DM.…”
Section: Introductionmentioning
confidence: 93%
“…This, in turn, modifies the expression of critical genes associated with physiological and pathological processes, including embryonic development, aging, and carcinogenesis [36,37]. There is growing evidence that folate modulates anticarcinogenic properties through epigenetic changes, as low folate intake has been associated with DNA hypomethylation and increased risk of colorectal and pancreatic cancers [37,38]. Diets rich in fruits and vegetables and containing natural antioxidants may protect against cancer.…”
Section: Transgenerational Effects Of Dietetic Factorsmentioning
confidence: 99%